2000
DOI: 10.1055/s-0037-1613993
|View full text |Cite
|
Sign up to set email alerts
|

Acquired von Willebrand Syndrome: from Pathophysiology to Management

Abstract: SummaryAcquired von Willebrand syndrome (AvWS) is a rare and probably underestimated bleeding disorder which mimicks most of the clinical symptoms and laboratory features of hereditary von Willebrand disease (vWD) in patients devoid of both personal and familial history of bleeding diathesis (1). AvWS and congenital vWD both result from a defect in von Willebrand factor (vWF), a large multimeric glycoprotein present in megakaryocytes, platelets, endothelial cells, subendothelium and mainly in plasma (2). vWF i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 130 publications
0
77
1
4
Order By: Relevance
“…Los mecanismos a través de los cuales se revertiría las manifestaciones clínicas de la EvW serían: 1) una liberación aumentada del FvW desde las células endoteliales dada por una mayor susceptibilidad a la epinefrina post terapia, 2) una estimulación no específica de la síntesis de proteínas hepáticas por acción de la tiroxina 21,22 .…”
Section: Discussionunclassified
“…Los mecanismos a través de los cuales se revertiría las manifestaciones clínicas de la EvW serían: 1) una liberación aumentada del FvW desde las células endoteliales dada por una mayor susceptibilidad a la epinefrina post terapia, 2) una estimulación no específica de la síntesis de proteínas hepáticas por acción de la tiroxina 21,22 .…”
Section: Discussionunclassified
“…19 Maintenance infusions of IVIg (1 g/kg) have been effective in a 2 patients, but lower doses (0.5 g/kg) failed. 19 Based on fewer than 5 cases in the literature, patients with IgM MGUS and AVWS do not respond to IVIg, 11,20 and would be appropriate candidates for aggressive VWF concentrate infusions, plasmapheresis, or extracorporeal immune absorption in addition to therapy targeted to the underlying plasma cell dyscrasia. Despite case reports of successful treatment with recombinant factor VIIa (rFVIIa) of AVWS associated bleeding refractory to IVIg, DDAVP, and FVIII/VWF concentrate, 21,22 it is premature to consider rFVIIa a standard treatment option.…”
Section: Disorders Of Primary Hemostasis and Acquired Von Willebrand mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Most reviews have concluded that AVWS is underdiagnosed and sometimes misdiagnosed, probably because of the broad spectrum of its clinical and laboratory features. Recent data suggest that AVWS is becoming more prevalent and that general hematologists are more likely to be referred patients with this condition.…”
Section: Introductionmentioning
confidence: 99%